PENGARUH PERPUTARAN KAS DAN PERPUTARAN PIUTANG TERHADAP LABA BERSIH PADA PT. INDOFOOD SUKSES MAKMUR TBK. PERIODE 2014 - 2023 - Noviyanti, Indri; Astuti, Widia (Journal of Research and Publication Innovation, 2024)
This research aims to determine the effect of Cash Turnover and Receivables Turnover on Net Profit at PT. Indofood Sukses Makmur Tbk. partially or simultaneously. The type of research carried out was quantitative descriptive with secondary data obtained from the PT Financial Report. Indofood Sukses Makmur Tbk. taken from the official website from 2014 to 2023. Data analysis methods using the Classic Assumption test technique include Normality test, Multicollinearity test, Heteroscedasticity test, and Autocorrelation test. As well as carring out Multiple Linear Regression Analysis technique, Correlation Coefficient test, Coefficient of Determination test, Hypothesis test (T Test), and Simultaneous test (F Test) with variable X1 Cash Turnover, variable X2 Receivables Turnover, and Variable Y Net Profit. All tests were carried out using the SPSS version 26 application. The results of the Cash Turnover research had no effect on Net Profit using the partial T test with a value of tcount < ttable, namely 0,570 < 2.365 and a significance value of 0.587 > 0.05. Receivables Turnover has no effect on Net Profit using the partial T test with a value of tcount < ttable, namely 1.300 < 2.365 and a significance value of 0.235 > 0.05. Cash Turnover and Receivables Turnover against Net Profit using the F test shows that the value of Fcount < Ftable is 0.886 < 4.74, with a significance of 0.454 > 0.05. So simultaneously Cash Turnover and Receivables Turnover together do not have a significant effect on Net Profit. The Multiple Linear Regression equation to determine whether Cash Turnover and Receivables Turnover have no effect on Net Profit is Y = – 2.477 + 0.091X1 + 0.263X2. The coefficient of determination is 20.20% and the remaining 79.80% is determined by other variables outside this research.